2016
DOI: 10.18632/oncotarget.14359
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 85 cases of intermediate-risk gastrointestinal stromal tumor

Abstract: Background & AimsA significant benefit of imatinib adjuvant therapy for patients with high risk gastrointestinal stromal tumors (GIST) has been confirmed. However, the effect of imatinib adjuvant therapy for intermediate-risk GIST has not been well studied. In this article, we compare differences of recurrence-free survival (RFS) rates between patients with intermediate-risk GIST who accepted imatinib adjuvant therapy and those who did not.MethodA retrospective study of intermediate-risk GIST was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although adjuvant therapy using imatinib for high-risk patients improves prognosis, some patients do not benefit from therapy due to toxicity. Furthermore, it remains unclear whether intermediate-risk patients with GISTs are candidates for adjuvant therapy [23]. Therefore, a more precise predictive marker is needed to select the patients who will receive significant benefit from adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although adjuvant therapy using imatinib for high-risk patients improves prognosis, some patients do not benefit from therapy due to toxicity. Furthermore, it remains unclear whether intermediate-risk patients with GISTs are candidates for adjuvant therapy [23]. Therefore, a more precise predictive marker is needed to select the patients who will receive significant benefit from adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As for Ki-67 proliferation, 10-year overall survival was 84% for patients rated <6% and 65% for those rated ≥6% (p=0.064). KaplanMeier plots are given in Figure 3A-C. and mitotic rate in GISTs (3,(15)(16)(17)(18)(19). Emory et al reported that survival rates were worst for patients with small bowel GIST tumors and best for those with esophageal ones (19).…”
Section: Survival Analysismentioning
confidence: 99%
“…Although Z9001 trial demonstrated that 1 year of adjuvant imatinib therapy could improve RFS of GIST patients [7], and SSGXVIII/AIO trial found that 3 years of imatinib therapy could improve RFS and overall survival of high risk GIST compared with 1 year Besides tumor size and mitotic index, location is also associated with the prognosis of GISTs, and nongastric GISTs were reported to be more aggressive than gastric GISTs in clinical course [12,13]. In the study reported by Fu et al [10], the prognosis of non-gastric GISTs was signi cantly worse than gastric GISTs. However, this has not been con rmed by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%